A CRITICAL ANALYSIS OF THE HIERARCHICAL CHURCH FROM THE PERSPECTIVE OF SERVICE LEADERSHIP (Hekima Review, 2023)
For an institution geared towards fulfilling its mission, quality leadership is a unifying symbol and assurance of attaining its goal. Every stable organization requires structures for proper functioning. However, overemphasis on the structures loses the focus on the mission, risks the danger of constitutionalism, and leaves the majority marginalized and dominated. This paper seeks to show that service leadership redirects the entire church institution toward the mission initiated by Christ with office and office bearers' consciousness of their mission as servants. This requires conversion and change of attitude for all.